Among the Moral Values in Pre-Islamic Poetry: An Objective Study - Mahgoub, Suad Sayed (Journal of Arabic Language Sciences and Literature, 2022)
The study analyzes some texts of pre-Islamic poetry and illuminated the core moral values that Bedouin man had. All in effort to motivate soul and mind with the importance of these values that Holy Quran also stressed on. So many platforms had dealt with the essences of moral values in different methods and approaches highlighting its importance within pagan societal hierarchy. The same society that prophet Mohammed (PBUH) born and grow-up in. This study has of two chapters, in which; had had addressed the moral values in pre-Islamic era linking and stressed on achieving peace and the core cultural virtues, leading to thriving society and resulted in attainment of Bedouin man aspirations.
Keywords: Moral values; pre-Islamic poetry; Peace and stability; Honors; virtues